75. Intraoperative monitoring in minimally invasive lateral transpsoas approach: Our experience. Issue 4 (April 2016) - Stipa, G.; Frondizi, D.; Fanelli, C.; Gobbi, D.; Mazzetelli, P.; Ciampini, A.; Carletti, S.
Abstract : The minimally invasive lateral transpsoas approach to the lumbar and spine has become an increasingly popular approach for achieving interbody fusion. The reported advantages include minimally invasive access to the spine, absent manipulation of aorta and vena cava, less blood loss compared to open procedures, decreased operative times, shorter hospital stays, less postoperative pain. The patient is placed in the lateral decubitus position. A lateral X-ray confirms that the patient is in a truly lateral position. A series of tubes and dilators are used to identify the mid-position of the disk to be incised. The dilator is introduced through a small incision and the surgeon's index finger directs the dilator through the retroperitoneal space to the psoas muscle. Due to the location of the lumbar nerve root contribution to the lumbosacral plexus within the psoas muscle, the risk of motor and sensory nerve injury is present when traversing the lumbosacral plexus with the dilator or during retractor positioning over the disk space. Neural monitoring (Free-Run EMG L2-S1 and intraoperative monopolar electrical stimulation, PEM and PES) is believed to be critical in localizing the lumbosacral plexus during positioning of the retractor system. We monitorized 15 patients with no complications.